The effect of preprocedural serum albumin to fibrinogen ratio on arteriovenous fistula maturation - Akgül, Engin; Özhan, Abdülkerim (Journal of Surgery and Medicine, 2021)
Background/Aim: Inflammation and inflammatory parameters are known to have unfavorable effects both on the surgical success and survival. The reference point of the present study are the results of an investigation of the effects of blood proteins such as albumin and fibrinogen, which affect blood viscosity, and other hematological parameters, on the success of arteriovenous fistula operations. Methods: This retrospective cohort study includes the data of 135 patients who underwent arteriovenous fistula surgery by the same surgeon in the same center. The patients were divided into two groups, as those with an active fistula 8–12 weeks after surgery and those with a dysfunctional fistula. After applying the exclusion criteria, the remaining data were compared using appropriate statistical methods to evaluate the influence on fistula maturation rates. Results: A statistical analysis performed after the evaluation of the fitness of the data to a normal distribution revealed fistula maturation to be associated with fibrinogen (P<0.001), albumin (P<0.001), fibrinogen-to-albumin ratio (FAR) (P<0.001) and neutrophil-to-lymphocyte ratio (NLR) (P=0.002). It was further noted that C-reactive protein (CRP) (P<0.001), CRP-to-albumin ratio (CAR) (P<0.001), neutrophil count (P=0.003) and lymphocyte count (P=0.03) all played a role in this process. A receiver operating characteristic (ROC) curve analysis revealed the cut-off values for fibrinogen (P<0.001, AUC: 0.930), CRP (P<0.001, AUC: 0.892), FAR (P<0.001, AUC: 0.988), CAR (P<0.001, AUC: 0.916), neutrophil count (P=0.011, AUC: 0.661) and albumin (P<0.001, AUC: 0.946) in terms of fistula maturation. Conclusion: The present study reveals that low albumin and high fibrinogen levels negatively affect AVF maturation. As reported previously in literature, and supported by the present study, high CRP levels may be associated with early AVF dysfunction.